STUBBLE BURNING IN DOBRUDZHA: RISK ANALYSIS FOR INFRASTRUCTURE AND CHERONEZH - Trizlova, Neli (E-Journal VFU, 2025)
The report examines the relationship between the agrotechnical practice of stubble burning and the catastrophic fire situation in Northeastern Bulgaria in 2025. The cumulative damage to the soil fertility of chernozems and critical infrastructure is analyzed. A scientific hypothesis is presented for the creation of "biological buffers" as a method of passive fire protection.
Keywords: stubble burning; impact on soil; biological buf